Life Skills Education in School Setting: A Review of Research in the Indian Context - Tiwari, Poonam; Bajpai, Anjali (INDIAN EDUCATIONAL REVIEW, 2021)
Life skills education is linked to almost all areas of human life, such as education, physical education, medical, psychology, mental health, sexual and reproductive health, wellness, environment, etc. Education has an abundant potential to develop life skills wherein, schools play an important role in the inculcation and internalisation of these life skills. So, more understanding is needed of the research held in the school area. The present review examined the literature on the status of life skills education in school settings with the view of gaining a comprehensive understanding and holistic picture of the status of life skills education in Indian schools and identifying research gaps and priorities. Seventy-seven studies were included for review, which was categorised into six different themes through content analysis. Findings reveal that a large number of studies focused on bringing in positive change in students’ attitudes and behaviour and enhancing their psycho-social competencies. Studies were also conducted to find out the status of life skills education in Indian schools and the curriculum and strategies to be adopted to internalise these skills. More research is needed to identify the problems with its implications. The review will be helpful in organising enriched programmes with effective life skills training for teachers and develop an effective life skills training module by involving major stakeholders for all the levels of education.